Linguistic Choices for Literary Dialectics: A Coming Together of Divergent Entities - Najeeb, Sabitha S. R.; AlDawood, Manar (European Scientific Journal, ESJ, 2016)
Literature involves the manipulation of language for creative purposes and the discipline which fosters this synergic relationship between literature and language is termed stylistics. The purpose of this article is to show how it is possible to bridge the divide between language and literature by using the analytical techniques available within this sub-discipline of language study. Stylistics aims to interconnect linguistic form and literary effect, and also account for what it is that readers respond to when they praise the quality of a particular piece of writing. This article attempts to depict how the knowledge of linguistic intricacies can affect the readerâ€™s interpretation. It also discusses how linguistic form relates to literary effect by analysing â€œDomination of Blackâ€, by the renowned American poet Wallace Stevens. We aim to show that a linguistic approach to the analysis of a literary text does not have to mean that interpretation is disregarded. On the contrary, stylistic analysis can often illuminate why a particular literary text is regarded so highly.